IDENTIFIKASI SEBARAN MINERAL BIJIH BESI DENGAN MENGGUNAKAN METODE RESISTIVITAS DAN INDUCED POLARIZATION (IP) DI KECAMATAN MUARA UYA, KABUPATEN TABALONG, PROVINSI KALIMANTAN SELATAN - Ferial, Deki; Natalisanto, Adrianus Inu (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
The geoelectric method is one of the geophysical methods. It studies the electrical properties on earth and detects on the surface of the earth. In this case includes the measurement of potential, currents and electromagnetic fields that occur either naturally or due to injection of current into the earth. This research was conducted at the mining site of PT. Bakal Makmur Sejahtera (BMS). Geographically, the mining location of PT. BMS is located at 173° 15' 32.8896